Intra-population variation of body temperature of the lizard Sceloporus anahuacus (Squamata: Phrynosomatidae) in Sierra del Ajusco, Mexico - Güizado-Rodríguez, Martha Anahí; García-Vázquez, Uri Omar; Solano-Zavaleta, Israel; Maceda-Cruz, Rolando Jonathan; Duifhuis-Rivera, Christopher (Instituto de Ecología, A.C., 2022)
We evaluated intra-population variation of body temperature of the Mexican lizard Sceloporus anahuacus (Phrynosomatidae) in Sierra del Ajusco, Mexico. The geographic distribution of this lizard is restricted to the higher parts of the mountains bordering the south of the Mexican Valley in Mexico City. The study of the body temperature of S. anahuacus and its relationship with the environment is important because high elevation taxa are seriously threatened by climate change. For that reason, and compared body temperature between sex, age class, reproductive condition and activity state. Overall, mean body temperature was 26.2 ± 5.5 °C with a range between 9–39 °C. We did not find differences between body temperatures of males and females. However, we found significant differences depending on activity state in both sexes. In females, body temperature did not vary as a function of age class or reproductive status. Instead, we found differences in body temperature between males of different age classes. Juveniles had the highest body temperature, probably due to differential temperature requirements associated with development. On the other hand, body temperature of active and inactive S. anahuacus was strongly associated with environmental temperature, perhaps due to sedentary habits and territorial behavior. Exploring why such variation exists on body temperature regulation may provide information on factors influencing the survivorship of this endemic Mexican lizard.